The Low-Latitude Ionosphere Sensor Network: Initial results - Valladares, C. E. (2012)
The Low-Latitude Ionospheric Sensor Network (LISN) is a distributed observatory designed to nowcast the state and dynamics of the low-latitude ionosphere and to develop forecasts of the electric fields, densities, and equatorial spread F over the South American continent. The LISN observatory consists of three different types of instruments: GPS receivers, fluxgate magnetometers, and vertical incidence pulsed ionospheric radar (VIPIR) ionosondes. This report provides a succinct summary of recent observations obtained using the LISN GPS receivers and complemented with measurements from other instruments and GPS receivers that operate in South America. More specifically, the following are shown here: (1) observations of total electron content (TEC) enhancements that occur near local midnight, (2) maps of TEC perturbations associated with the passage of traveling ionospheric disturbances over South America, and (3) statistics of TEC depletions for 2 years of low solar activity. Near-midnight TEC enhancements consist of sudden increases in TEC that occur after sunset at low latitudes on 30% of the days. These TEC enhancements last for several hours and can have amplitudes between 1 and 50 TEC units. On 11–12 March 2011 the largest TEC enhancement was observed in South America at times when the Jicamarca incoherent scatter radar operated and observed peak densities above 106 el/cc at 300 km altitude. It is suggested that a combination of zonal electric fields and meridional neutral winds are able to redistribute the plasma along the field lines and create regions of enhanced TEC. Maps of TEC perturbations associated with the passage of gravity waves (GWs) over South America have been used to measure the phase velocity and direction of propagation of GWs. The large number of GPS receivers over South America has allowed us to record bubble events for every day during 2008 and 2009. It was found that the number of TEC depletion detections varies with a periodicity of 28 days. It is mentioned how these new observations and the installation of the last four VIPIR ionosondes will lead to new discoveries in the near future.